PENERAPAN PENDIDIKAN KARAKTER PADA ANAK USIA DINI DI TK ISLAM ASH-SHIBGOH DIDESA KALIJAGA TAHUN 2024 - Ni'Matul Khaer; Abdul Kadir Jaelani; Muhammad Tahir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the implementation of character education in early childhood at Ash-Shibgoh Islamic Kindergarten, Kalijaga Village. Character education has an important role in shaping children's personalities, especially at the age of 0-6 years which is known as the